Third Ventricle Craniopharyngioma Intraventricular Tumor: A Case Report and a Brief Literature Review - Ferreira Neto, Otávio da Cunha; Braun, Débora Mendes; Dias, Artêmio José Araruna; Lemos, Nilson Batista; Diniz, Andrey Maia Silva; Lima, Luís Felipe Gonçalves de; Alencar Neto, Joaquim Fechine de; Cabral, Bianca Domiciano Vieira Costa; Andrade, Jonas Silva; Clemente, Rafaelly Maia; Bem Junior, Luiz Severo Bem; Almeida, Nivaldo Sena; Azevedo Filho, Hildo Rocha Cirne (Journal of Neurological Surgery Reports, 2022)
Craniopharyngioma is a rare embryonic malformation, usually benign, of the sellar or parasellar regions. In this study, an uncommon case of third ventricle craniopharyngioma and a succinct review of its prevalence are presented. Even with low mortality rates, these injuries involve a high degree of endocrinological, visual, and neuropsychological morbidities, which have a huge impact on the patient's quality of life. Thus, surgical resection is the preferred therapy for tumors that compromise the flow of cerebrospinal fluid. However, due to the location of the craniopharyngioma, surgical management is accompanied by the risk of injury to important adjacent areas with postoperative repercussions. Therefore, the neurosurgeon's experience and the choice of the best surgical approach, are crucial for increasing prognosis.
Keywords: craniopharyngioma; third ventricle; cerebral ventricle neoplasms; neurosurgery